Pelatihan Teknik Fotografi Produk Iklan UMKM di Kelurahan Jatinegara Kaum - Wiratri Anindhita; Eliana Sari; Khoirul Muttaqin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The closing of the Implementation of Restrictions on Community Activities (PPKM) during the Covid-19 pandemic by the government in Indonesia became the starting point for the rise of Micro, Small and Medium Enterprises (MSMEs) actors. So, to run a business again, MSMEs need marketing innovations that are adapted to technological advances. However, not many of MSME business actors use digital media technology for marketing their products. Therefore, this community service activity aims to provide knowledge and training in advertising design photography as a brand management strategy and as well as marketing communications to MSME business actors in Jatinegara Kaum. The training begins with an explanation regarding effective business communication when marketing a product or service. After that, it was continued by providing material related to soft selling techniques in brand management which was then carried out in practice. The method of implementing this training is carried out with questions and answers, demonstrations, direct practice and evaluation. The results of this training show that using a camera as a product promotion tool does not require a high price. Instead, MSME business actors can use their cellphones to take photos of these products with the right technique.